The security risk handbook : assess, survey, audit - Swanson, Charles (Chartered Security Professional) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
The Security Risk Handbook assists businesses that need to be able to carry out effective security risk assessments, security surveys, and security audits. It provides guidelines and standardised detailed processes and procedures for carrying out all three stages of the security journey: assess, survey, and audit. Packed with tools and templates, the book isextremely practical. At the end of each explanatorychapter, a unique case study can beexamined by the reader in the areas of risk assessment, security survey, and security audit. This book also highlights the commercial and reputational benefits of rigorous risk management procedures. It can be applied to corporate security, retail security, critical national infrastructure security, maritime security, aviation security, counter-terrorism, and executive and close protection. This text is relevant to security professionals across all key sectors: corporate security, retail security, critical national infrastructure security, maritime security, aviation security, counter-terrorism, and executive and close protection. It will also be useful to health and safety managers, operations managers, facilities managers, and logistics professionals whose remit is to ensure security across an organisation or function.
OCLC-licensed vendor bibliographic record.
Keywords: Corporations -- Security measures; Business enterprises -- Security measures; Computer security; Risk management; BUSINESS & ECONOMICS / Infrastructure; BUSINESS & ECONOMICS / Insurance / Risk Assessment & Management; BUSINESS & ECONOMICS / Facility Management